Study on Control Strategy for Wind Driven Generator Considering Power System Stability. Issue 6 (April 2019) - Lu, Qifu; Liu, Zhengfu; Kong, Xiangyu; Wang, Hongxing; Sheng, Chao; Zhao, Chang
Abstract: Wind power has random fluctuations and intermittent as a way of renewable energy generation. This paper uses a model of multi-state unit to equivalent the transmission grid system include wind power generation considering the influence of increasing capacity of wind farm connection on the reliability of distribution system. A hybrid system dispatching model of double-fed wind turbine is proposed based on the analysis of the structure of double-fed wind turbine and the outage model of fan and conventional unit. In order to maximize the use of wind based on the constraints of the power system, the base load of conventional units such as thermal power units are used first, and then the wind power is used as a priority to minimize the entire power generation cost. At the same time, the output of the wind power unit is constrained by the penetration power limit that the influence of wind power randomness on the safe and stable operation of the system is considered. The simulation results show that this control strategy can keep frequency by change the velocity, track the maximum wind energy, adjust the power factor and stabilize the voltage of the power grid.